1988
DOI: 10.1177/026765918800300407
|View full text |Cite
|
Sign up to set email alerts
|

The use of the Hemochron in assessment of heparin reversal after cardiopulmonary bypass

Abstract: The use of the Hemochron activated clotting time (ACT) for determining adequacy of reversal of heparin following cardiopulmonary bypass was evaluated in 20 patients and compared with standard laboratory tests of coagulation. The commonly used Celite ACT method proved too insensitive to have any useful predictive value in detecting or quantifying residual heparin and removal of the Celite activation rendered the test even less sensitive. In contrast, the partial thromboplastin time with kaolin (PTTK) proved to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Despite the popularity ofthe ACT, there is still debate over its usefulness. Several studies have found that the ACT does not show a good correlation with the plasma heparin levels (13,27), and that the ACT had little value on residual heparin levels (28,29). Dietrich, on the other hand, found that the plasma heparin level itself was not a good indicator of anticoagulation (25).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the popularity ofthe ACT, there is still debate over its usefulness. Several studies have found that the ACT does not show a good correlation with the plasma heparin levels (13,27), and that the ACT had little value on residual heparin levels (28,29). Dietrich, on the other hand, found that the plasma heparin level itself was not a good indicator of anticoagulation (25).…”
Section: Discussionmentioning
confidence: 99%
“…Rather than reducing the ACT toward 123 s (poststernotomy baseline), supplemental protamine increased ACT to 161 s. This suggests that heparin was already either fully neutralized or overneutralized, because excessive protamine increases ACT (15,16). Although relative insensitivity to heparin favors the ACT for monitoring anticoagulation during CPB, it diminishes its ability to diagnose incomplete heparin neutralization after CPB adequately (6,18,19). If hemostasis had been inadequate in patient C, the comparison of sternotomy and postprotamine ACTS would have suggested the need for clotting factors, platelets, or possibly desmopressin.…”
Section: Discussionmentioning
confidence: 99%
“…If hemostasis had been inadequate in patient C, the comparison of sternotomy and postprotamine ACTS would have suggested the need for clotting factors, platelets, or possibly desmopressin. Consequently, to maximize the post-CPB diagnostic utility of a relatively imprecise test (9) that lacks sensitivity to low concentrations of heparin (6,18,19), pre-CPB baseline ACT is best obtained after surgical incision. Activated coagulation time functions well as a monitor of CPB anticoagulation because it is relatively insensitive to heparin.…”
Section: Discussionmentioning
confidence: 99%